A Pilot Study on Structural Responses of Normal Concrete-UHPC Composite Bridge Decks w/wo Rebars through an Experimental-Numerical Approach - Siqi Yuan; Zhao Liu; Teng Tong; Chung C. Fu (Advances in Civil Engineering)
Ultra-high-performance concrete (UHPC) is already gaining in-field applications in bridge deck rehabilitation. On the other aspect, an innovative NC-UHPC composite deck system was motivated to promote accelerated bridge construction (ABC) implementation of a newly built bridge, of which the precast UHPC substrate serves as the formwork for the cast-in-place NC overlay. Performance characterizations were investigated by loading five decks, of various UHPC thickness and w/wo longitudinal or transverse rebars. Their effects on the composite decks’ failure patterns and load-deflection curves were quantitatively analyzed. Besides, digital image correlation (DIC) technique was adopted to adequately capture their damage evolutions. Moreover, analytical solutions for predicting a composite deck’s flexural and shear strengths are tentatively derived. Finally, 3D finite element (FE) models are developed within ATENA framework, capable of embracing the NC-UHPC interface’s behaviors. Numerical predictions agree well with the experimental results and can benefit further researches evolving a NC-UHPC composite deck system.